PENGGUNAAN DATA IKLIM DAN TANAH UNTUK PENENTUAN POLA TANAM PADI, UBI KAYU DAN KEDELAI DI KECAMATAN PANGGANG DAN RONGKOP, GUNUNGKIDUL - , BINTANG SUKMA MUKTI, Ir. Mulyono Nitisapto, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the level of potential land in accordance with the conditions required for rice, cassava, and soybeans at Panggang and Rongkop Districts, Gunungkidul and planting pattern in accordance with the existing weather data. The field research was conducted during January 2013 and laboratory analysis conducted in February and March 2013 at the Kuningan Soil Laboratory, General Soil Laboratory, and Soil Physics Laboratory Department of Soil, Faculty of Agriculture, Gadjah Mada University, Yogyakarta. Determination of the level of potential land was carried out by using a simple limitation method using rainfed rice growing conditions, cassava and soybeans by Djaenudin et al., (2003). Cropping pattern was determined by comparing the average evapotranspiration and rainfall. Results showed that the analysis of potential land suitability for rice S3eh1 25.56% and 74.44% Neh1, cassava S3rc1 0.469%, 28.62% S3rc1eh1, and Neh1 70.91%, and 0.47% soybean S2eh1lp2, S3eh1 26.64%, 2.34% S3rc3eh1, and 70.56% Neh1. The main limiting factor was slope (eh1). Cropping patterns for those two districts at the first planting season is multiple cropping of rice and cassava and the planting season II is soybean and cassava. Planting season in Panggang began at October 2nd ten-days, while Rongkop at October 3rd ten-days.